Nursing Diagnosis in Perioperative Cataract and Comorbidity - Ana Zakiyah; Chaterina Janes Pratiwi; Tiwuk Styowati (Journal of Ners and Midwifery, 2023)
Nurses are essential in providing nursing care to patients for pre, intra, and postoperative cataracts. An appropriate nursing diagnosis can help clients achieve optimal health. The purpose of the study was to identify nursing diagnoses in pre,intra, and postoperative cataracts. The design of the study used qualitative descriptive research design. The population of all patients undergoing surgery was 30, and data was collected through interviews and observations. The results of the study: preoperative nursing diagnosis consisted of sensory perception and anxiety disorders 30 (100%), impaired physical mobility, activity intolerance, and risk of falling 3 (10%), knowledge deficit 2(6,7%), body image disorders 1 (3,3%). Intraoperative nursing diagnosis: impaired tissue integrity 30 (100%), acute pain 7(23,3%), hypothermia 4 (13%), hypothermia risk 3 (10%). Postoperative nursing diagnosis, all participants experienced sensory perception disorders 30 (100%), acute pain 7(23.3%), infection risk 5(16,7%), impaired physical mobility, activity intolerance and fall risk 3 (10%), knowledge deficit 2(6.7%). Comorbidity affects the enforcement of nursing diagnoses. The correct nursing diagnosis is a reference for nurses in providing continuous intervention so that quality nursing services are obtained